Understanding the fermentation factors affecting the separability of fermented milk: A model system study. (October 2021) - Priyashantha, Hasitha; Buldo, Patrizia; Berg, Thilo; Gilleladen, Christian; Ipsen, Richard
Abstract: The demand for high-protein fermented milk products is globally increasing. The effect of added starter culture, cutting pH and fermentation temperature on separability, i.e., how well curd and whey separate, were evaluated in a model system aiming to resemble Greek-style yoghurt. Skim milk was fermented with three commercial starter cultures at 39 °C or 43 °C to a pH of 4.45 or 4.60. Stirred fermented gels were concentrated to produce high-protein (~10%) fermented milk. The starter culture influenced the microstructure as well as the association (interactions) between exopolysaccharides (EPS) with the surface of the protein aggregates. The high association of EPS increased the viscosity and gel strength of the fermented model gels and decreased the zeta potential, the amount of whey removed as well as the protein and total solids concentration in the white mass. Increased fermentation temperature (from 39 °C to 43 °C) resulted in increased particle size and zeta potential values when EPS-producing starter cultures were applied. Cutting pH did not influence the separability of fermented stirred gels. The presence of EPS and pronounced association with protein increased the particle size, negative surface charge and structural rigidity, establishing a more stable system with reduced separability. Graphical Abstract: ga1 Highlights: The separability of fermented milk in concentrated yoghurt production was tested. Separability is affected by the type of starter culture, fermentation temperature but not the pH. Exopolysaccharide (EPS) association with protein creates a stable system. High EPS association increased the viscosity, zeta potential and particle size. Interactions and association of EPS with protein aggregates decreased separation.